Caregiving concerns and clinical characteristics across neurodegenerative and cerebrovascular disorders in the Ontario neurodegenerative disease research initiative. (27th May 2022) - Beaton, Derek; McLaughlin, Paula M.; Orange, Joseph B.; Munoz, Douglas P.; Mandzia, Jennifer; Abrahao, Agessandro; Binns, Malcolm A.; Black, Sandra E.; Borrie, Michael; Dowlatshahi, Dar; Freedman, Morris; Fischer, Corinne E.; et al.
Abstract: Objectives: Caregiving burdens are a substantial concern in the clinical care of persons with neurodegenerative disorders. In the Ontario Neurodegenerative Disease Research Initiative, we used the Zarit's Burden Interview (ZBI) to examine: (1) the types of burdens captured by the ZBI in a cross‐disorder sample of neurodegenerative conditions (2) whether there are categorical or disorder‐specific effects on caregiving burdens, and (3) which demographic, clinical, and cognitive measures are related to burden(s) in neurodegenerative disorders? Methods/Design: N = 504 participants and their study partners (e.g., family, friends) across: Alzheimer's disease/mild cognitive impairment (AD/MCI; n = 120), Parkinson's disease (PD; n = 136), amyotrophic lateral sclerosis (ALS; n = 38), frontotemporal dementia (FTD; n = 53), and cerebrovascular disease (CVD; n = 157). Study partners provided information about themselves, and information about the clinical participants (e.g., activities of daily living (ADL)). We used Correspondence Analysis to identify types of caregiving concerns in the ZBI. We then identified relationships between those concerns and demographic and clinical measures, and a cognitive battery. Results: We found three components in the ZBI. The first was "overall burden" and was (1) strongly related to increased neuropsychiatric symptoms (NPI severity r = 0.586, NPI distress r = 0.587) and decreased independence in ADL (instrumental ADLs r = −0.566, basic ADLs r = −0.43), (2) moderately related to cognition (MoCA r = −0.268), and (3) showed little‐to‐no differences between disorders. The second and third components together showed four types of caregiving concerns: current care of the person with the neurodegenerative disease, future care of the person with the neurodegenerative disease, personal concerns of study partners, and social concerns of study partners. Conclusions: Our results suggest that the experience of caregiving in neurodegenerative and cerebrovascular diseases is individualized and is not defined by diagnostic categories. Our findings highlight the importance of targeting ADL and neuropsychiatric symptoms with caregiver‐personalized solutions. Key points: We identified multiple types of caregiving burden from the Zarit's Burden Interview across five neurodegenerative and cerebrovascular disorders. Overall burden showed strong relationships with neuropsychiatric symptoms (measured via Neuropsychiatric Inventory ‐ Questionnaire) and functional dependence (measured via instrumental and basic activities of daily living (ADL)). We found little to no differences between disorders. Through our analyses we identified two questions that stood out with very high responses, and these two questions briefly capture the four types of burdens we identified: "Are you afraid of what the future holds for your relative?" and "Do you feel your relative is dependent on you?".